2000
DOI: 10.1148/radiology.215.1.r00ap08153
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Hepatic US with Microbubble Contrast Agent: Initial Experience Showing Improved Characterization of Hemangioma, Hepatocellular Carcinoma, and Metastasis

Abstract: Contrast-enhanced harmonic imaging appears superior to conventional Doppler US for hepatic mass characterization. Low-MI continuous and high-MI interval-delay imaging can help assess tumor vascular pattern and microvascular volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
159
1
12

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(179 citation statements)
references
References 9 publications
7
159
1
12
Order By: Relevance
“…258,259,261 The technology of ultrasound diagnosis is evolving rapidly; it is anticipated that advances such as microbubble contrast enhancement and harmonic imaging techniques will significantly improve early detection rates in coming years. [263][264][265][266] There is also a possibility that these developments will raise false-positive findings.…”
Section: Ultrasonographymentioning
confidence: 99%
“…258,259,261 The technology of ultrasound diagnosis is evolving rapidly; it is anticipated that advances such as microbubble contrast enhancement and harmonic imaging techniques will significantly improve early detection rates in coming years. [263][264][265][266] There is also a possibility that these developments will raise false-positive findings.…”
Section: Ultrasonographymentioning
confidence: 99%
“…However, contrast-enhanced color or power Doppler sonography with microbubble agents has shown several limitations, including blooming artifacts of contrast agents and motion artifacts by cardiac pulsation. 6,[22][23][24][25] Some recent studies have reported that interval delay imaging using a pulse inversion harmonic technique is superior to conventional Doppler sonography for assessing tumor vascularity, 11,12,26 but despite these recent applications of intermittent imaging, most radiologists prefer to scan in a continuous mode.…”
Section: A B C D E Fmentioning
confidence: 99%
“…In addition, coupling conventional color Doppler with a US contrast medium allows only the macrovasculature of the lesions to be displayed because with continuous insonation the bubbles are continuously destroyed in larger vessels and thus never reach the smaller downstream vessels. 4 If the aim of the study by Fracanzani et al was especially to differentiate hepatocellular carcinomas from either atypical or benign nodules by showing subtle differences in microvasculature, then the method used by Fracanzani et al is clearly too rough and inaccurate.…”
Section: Liver Nodule and Us Medium Contrast Agents: Past And Futurementioning
confidence: 99%
“…[3][4][5] The new strategies for tissue characterization of liver nodules (in either a normal or cirrhotic liver) entails the combination of wide-band harmonic imaging, US contrast agents at high and low mechanical index, and different scanning techniques (e.g., intermittent imaging, pulse inversion).…”
Section: Liver Nodule and Us Medium Contrast Agents: Past And Futurementioning
confidence: 99%
See 1 more Smart Citation